Penerapan model pembelajaran scramble untuk meningkatkan motivasi belajar ips peserta didik di sekolah dasar - Anggita Nissa Gravitiani; Siti Istiyati; Siti Kamsiyati (Didaktika Dwija Indria, 2022)
Abstract. The purpose of this study is to increase the motivation for IPS learning through the application of a scramble learning model to students in Grade IV of Krasak Boyolali State Elementary School in the 2021/2022 academic year. This study is a class action study (PTK) consisting of two cycles in which each cycle consists of two encounters and each cycle consists of four stages of action: planning, implementation, observation, and reflection. The subjects in this class action study are class IV class 1 student Krasak Boyolali Krasak, in the 2021/2022 school year. The number of research subjects is 9 research subjects. Data collection techniques by observation, retrieval, interviews and documentation. The tests of data validity in this study are source triangulation and engineering triangulation. The data analysis techniques used in this study used the Milles and Huberman analysis model consisting of data collection, data reduction, data display, and conversion drawing/verification. The results of the assessment show an improvement in the learning motivation of the student is evidenced by the increase in the presentation results of the study motivation set of the student, observation result and test scores of the student starting from preaction, cycle I, and cycle II. Based on the results from the study, the average percentage of participants' motivation score was 56.91% at the time of pre-action, then cycle I was 73.29%, and cycle II was 88.79%. The results of this study show that there has been an increase in each cycle of research action. This study concludes that the application of the scramble learning model can increase the learning motivation of students in Grade IV of Krasak Boyolali State Elementary School in the 2021/2022 school year.